The Impact of Gold Nanoparticle Susceptibility on Drug Resistance Phenotypes in Uropathogenic Escherichia coli - Iman Hosseinpour1; Leila Fozouni1*; Morteza Khademi1; Mehdi Movaghari1; Mohammad Mehdi Akhoondi1 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: The widespread use of antibiotics has contributed to the dissemination of multidrug-resistant pathogens. This study aimed to assess the prevalence of Escherichia coli strains associated with urinary tract infections, characterized by diverse drug-resistance phenotypes. Additionally, the antibacterial properties of gold nanoparticles were examined against each phenotype to determine their effectiveness. Methods: This cross-sectional study was conducted on 170 E. coli strains isolated from 250 urine samples collected from symptomatic and asymptomatic patients with urinary tract infections (UTIs) between August 2022 and July 2023. The antibiotic susceptibility profiles across various classes of antibiotics were determined using the Kirby-Bauer method. At the same time, the minimum inhibitory concentrations of gold nanoparticles were assessed through the microdilution broth test. Results: Among E. coli isolates, 91 (53.53%), 45 (26.47%), and 17 (10%) isolates were identified as multidrug-resistant (MDR), extensively drug-resistant (XDR), and pandrugresistant (PDR), respectively. The MIC of gold nanoparticles that inhibited the growth of 90% of PDR isolates (MIC90=200 ppm) was two times higher than the MIC90 against XDR isolates (MIC90=100 ppm) and four times higher than the MIC90 against MDR isolates (MIC90=50 ppm). There was also a significant difference between the MIC90 and the MIC of gold nanoparticles that inhibited the growth of 50% of PDR and XDR bacteria (P<0.05). Conclusion: The emergence of MDR, XDR, and PDR uropathogenic E. coli isolates represents a significant societal health concern. Considering the favorable in vitro antimicrobial potential of gold nanoparticles against uropathogenic E. coli isolates, it is recommended to further analyze their applicability as antibiotic alternatives by conducting in vivo studies.